Garbage and Recycling - Haerens, Margaret (Opposing viewpoints, 2012)
"Garbage and Recycling: Is Garbage a Serious Problem?; Is Recycling Effective?; Is Toxic Waste Disposal a Serious Problem?; What Strategies Will Help Reduce Waste and Save Money?"-- Provided by publisher